Cultural Conflicts in the Work of N. Scott Momaday - Tonarová, Ivona (Univerzita Pardubice, 2013)
The main aim of this paper is the analysis of the work of N. Scott Momaday, mainly his novel House Made of Dawn. The first part of the paper is focused on Native American literature. The life and the work of N. Scott Momaday are briefly described. The theoretical part further provides readers with the historical and cultural context of the novel. It is focused on the history of White-Indian relations, Indians' participation in World War II and it explains the term cultural conflict. The second part describes the life on a reservation and examines the cultural conflicts in the novel.
Kulturní konflikty v práci N. Scott Momaday
Keywords: Momaday, N. Scott; Dům z úsvitu; americká indiánská literatura; indiáni; kulturní konflikt; Momaday, N. Scott; House Made of Dawn; Native American Literature; Indians; cultural conflict